Intentional Author as a Subject of Virtual Communication (Content of Corporate Websites News) - Kim, L. G.; Ustinova, M. V. (Nauc̆nyj dialog (Online), 2024)
This study explores the “image of the virtual intentional author” in the news discourse of corporate websites. A comparative analysis of materials from corporate websites of Kemerovo State University and Siberian Coal and Energy Company is conducted. Subjective, predicate-actant, and locative-temporal components are identified. Typical and specific semantic components are named. The typical shared components include the following meanings: “I am a significant subject of the Russian space”; “I represent a collective of professionals”; “I engage in volunteer and charitable activities”. Each of the considered organizations’ intentional author image is characterized by specific features. The intentional author of the university’s news content realizes the following modal meanings: “I am not only a leading university in the region but also part of global rankings, serving as a center for scientific, social, volunteer activities, etc. in the region”, thus, the virtual author communicates the intention to present the university as a significant subject of the Russian educational space. The   intentional author of the energy company’s news content conveys meanings such as: “I am the best production organization”; “I am competitive”; “I am socially oriented”; “I interact with authorities and public organizations”.